MIŠLJENJA I STAVOVI RAZREDNIH UČITELJA PREMA VREDNOVANJU (EVALUACIJI) I OCENJIVANJU U NASTAVI FIZIČKOG VASPITANJA - Enver Međedović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
By this research have been included all candidates at the Entrance examination of the Teachers' University from Belgrade, who made the sample of the 80 examined. This research was done in the school year 2005/06.Through this interdisciplinary research, candidates for the entrance have answered on several questions concerning of giving the importance in some segments of education, physical culture, sociological and economy aspect, which influence on proper development of a personality. Data have been collected with a survey and with a help of a questionnaire, consisting of 15 questions; and in the end in a specially offered space, candidates have given their suggestions concerning the Teachers' University (why they have chosen this University, public or private, questions connected with improvement of sport and physical culture).